Insights into human kidney function from the study of Drosophila - Koehler, Sybille; Huber, Tobias B. (Pediatric nephrology (Berlin, West), 2023)
Biological and biomedical research using Drosophila melanogaster as a model organism has gained recognition through several Nobel prizes within the last 100 years. Drosophila exhibits several advantages when compared to other in vivo models such as mice and rats, as its life cycle is very short, animal maintenance is easy and inexpensive and a huge variety of transgenic strains and tools are publicly available. Moreover, more than 70% of human disease-causing genes are highly conserved in the fruit fly. Here, we explain the use of Drosophila in nephrology research and describe two kidney tissues, Malpighian tubules and the nephrocytes. The latter are the homologous cells to mammalian glomerular podocytes and helped to provide insights into a variety of signaling pathways due to the high morphological similarities and the conserved molecular make-up between nephrocytes and podocytes. In recent years, nephrocytes have also been used to study inter-organ communication as links between nephrocytes and the heart, the immune system and the muscles have been described. In addition, other tissues such as the eye and the reproductive system can be used to study the functional role of proteins being part of the kidney filtration barrier.